Evaluation of various turbulence models for numerical simulation of a multiphase system in a rotating packed bed. (15th November 2019) - Ouyang, Yi; Tang, Kai-Liang; Xiang, Yang; Zou, Hai-Kui; Chu, Guang-Wen; Agarwal, Ramesh K.; Chen, Jian-Feng
Highlights: The Wray–Agarwal model was successfully implemented in a multiphase system in RPB. Numerical results based on the Wray–Agarwal model were validated. Flow characteristic and polymerization process in the RPB were revealed. Turbulent characteristics with various turbulence models were evaluated. Abstract: Numerical simulations of a multiphase system (synthesis of butyl rubber) in a rotating packed bed (RPB) are reported in this paper. Several turbulence models, namely the Standard k-ε, Realizable k-ε, SST k-ω, RSM, and the recently developed one-equation Wray–Agarwal (WA) turbulence model are used in conjunction with the Reynolds-Averaged Navier-Stokes equations. WA model has been shown to be quite accurate and efficient in a large number of benchmark (50+) wall bounded and free shear flows. In this paper for the first time, WA model coupled with Eulerian multiphase model is successfully implemented to simulate the complex multiphase system RPB. Employing the experimental data available in the literature, numerical results are validated based on the liquid holdup in the RPB and the average molecular weight ( Mn ) of the butyl rubber. Flow characteristic and polymerization process in the RPB are obtained. The WA model results are compared with those obtained with the Standard k-ε, Realizable k-ε, SST k-ω and RSM models.